The Role of Artificial Intelligence in Supporting Development in Emerging Markets - Strusani, Davide; Houngbonon, Georges Vivien (International Finance Corporation, Washington, DC, 2019)
Artificial intelligence (AI) has enormous potential to augment human intelligence and to radically alter how one access products and services, gather information, make products, and interact. In emerging markets, AI offers an opportunity to lower costs and barriers to entry for businesses and deliver innovative business models that can leapfrog traditional solutions and reach the underserved. With technology-based solutions increasingly important to economic development in many nations, the goals of ending poverty and boosting shared prosperity may become dependent on harnessing the power of AI. While emerging markets are already using basic AI technologies to solve critical development challenges, much more can be done, and private sector solutions will be critical to scaling new business models, developing new ways of delivering services, and increasing local markets’ competitiveness. All of these solutions require innovative approaches to expand opportunities and mitigate risks associated with this new technology.